Impact of Physical Exercise on Symptoms of Depression and Anxiety in Pre-adolescents: A Pilot Randomized Trial - Philippot, Arnaud; Meerschaut, Alexandre; Danneaux, Laura; Smal, Gauthier; Bleyenheuft, Yannick; De Volder, Anne G. (Frontiers in Psychology, 2019)
Aim: The investigators documented the effectiveness of different training intensities in reducing symptoms of depression and anxiety amongst pre-adolescents. Method: The study included twenty-seven, randomly selected pre-adolescents (aged between 9-11 years of age) all of whom had Primary education. The participants were enrolled and, over a five-week period, were subject to either intensive or low-to-moderate exercise programmes four times a week. Psychological self-reports, as well as physical examinations, were conducted before and after such programmes in blinded assessments. Psychological effects were considered the primary outcome, whilst physical condition was secondary. Results: Four subjects were lost and twenty-three were analyzed. General linear model with 2 criteria revealed significant changes (p=0.05) in trait anxiety symptoms over time in the low-to-moderate intensity group (LMIG). Within group changes followed a significant decrease in levels of anxiety (38,82 ± 2,20 to 33,36 ± 2,83 p=0,004) and depression (10,36 ± 2,83 to 6,73 ± 1,88 p=0.006) related symptoms amongst those in the LMIG. Interpretation: This study indicated that depression and anxiety symptoms were reduced amongst a non-clinical sample of Primary educated pre-adolescents when they were subject to a low-to-moderate exercise programme. The programme focused on associating movement with pleasure, and encouraged positive, non-competitive interactions between participants